Stabilization of rammed earth with waste materials for sustainable construction under rainfall Conditions: With consideration of life cycle assessment (LCA) - Alireza Komaei; Aneseh Mosaddegh; Mahdi Hemmati; Ahmad Fahimifar (Developments in the Built Environment, 2025)
This study proposes a stabilization strategy for rammed earth, addressing the critical need to enhance its resilience against extreme weather, particularly heavy rainfall. By incorporating recycled carpet waste fibers and alkali-activated materials (AAMs), the research shows a threefold increase in unconfined compressive strength compared to compacted unstabilized soil. The use of AAMs as a low-carbon alternative to cement reduces environmental impact, while carpet waste fibers contribute to a circular economy by repurposing textile waste. Durability tests under severe rainfall revealed that the stabilized material retained 99 % of its compressive strength, while unstabilized rammed earth lost 28 %. Additionally, the stabilized material exhibited a fourfold increase in tensile strength. This method also significantly improved toughness and brittleness index, maintaining performance under harsh rainfall conditions. Microstructural analysis revealed improved bonding and densification, enhancing long-term durability. This research advances sustainable construction by integrating waste valorization and low-carbon technologies to create resilient, eco-friendly earthen structures.